(untitled) (International Journal of Environmental Sciences, 2024)
National constitution is a living organism, it must also be allowed to grow, develop and change like any other living thing in tune with the changing phenomenon, but in the name of change, it must not be allowed to destroy the document. During the passage of time, the scope of judicial review inter alia judicial activism has ever been expanded because of its peremptory nature in a parliamentary democracy, and mistrust between the elected legislature and unelected judges of the Supreme Court has also been increasingly witnessed, specially in the matter of the constituent power. The article dwells upon the relative implications of basic structure doctrine propounded by judiciary and also probable premises for unabated mistrust lingering between the two constitutional pillars. It also focuses on the emerging concept of juridical landscape in the light of sustaining a meaningful constitutional government without scarifying the vibrant democracy.